A crucial factor affecting the power conversion efficiency of oxide/metal/oxide-based organic photovoltaics: Optical cavity versus transmittance. (1st February 2019) - Lee, Byeong Ryong; Park, Gi Eun; Kim, Yong Woon; Choi, Dong Hoon; Kim, Tae Geun
Graphical abstract: We display a crucial factor that dictates the power conversion efficiency (PCE) of OMO-based OPVs by investigating the effect of photon fields in the active region and the transmittance of the electrode on the PCE of ZnO/Ag/ZnO-based OPVs with top ZnO layers of varying thicknesses. One of the optimized OPVs exhibit record-high PCE and mechanical flexibility in these devices. Highlights: Structure for organic photovoltaics with ZnO/Ag/ZnO electrodes is optimized. Crucial factor dictating power conversion efficiency is identified in these devices. High power conversion efficiency (8.71%) is achieved from organic photovoltaics. Excellent mechanical flexibility is also observed. Abstract: Considerable effort has been directed at improving the power conversion efficiency of organic photovoltaics, using oxide/metal/oxide multilayers as transparent electrodes, because of their numerous advantages including lower sheet resistance, higher transmittance, and higher flexibility in comparison to typical indium tin oxides. However, to date, most organic photovoltaics based on oxide/metal/oxide electrodes exhibit a lower conversion efficiency than indium tin oxide-based organic photovoltaics, without any clarification. In this investigation, we identify crucial factors that influence the power conversion efficiency of oxide/metal/oxide-based organic photovoltaics to fully exploit the potential of these devices, based on the correlation between the optical cavity and the transmittance. For this purpose, we fabricate five sets of inverted organic photovoltaics using poly(4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3, 4- b ]thiophenediyl) and [6, 6]-Phenyl C71 butyric acid methyl ester-based active layers and ZnO/Ag/ZnO electrodes with top ZnO layers of varying thicknesses, with reference organic photovoltaics using indium tin oxides, on both rigid and flexible substrates. The highest power conversion efficiency of 8.71% and 7.53% is obtained from single-junction organic photovoltaics with 40/9/8-nm-thick ZnO/Ag/ZnO electrodes on each substrate, due to strong micro-cavity effects between the top and bottom Ag layers, despite the relatively low transmittance of the electrode. This result is supported by the relation between the electric-field intensity and the transmittance curves of the ZnO/Ag/ZnO/solution-based ZnO/active bulk optical stacks based on simulation results. Furthermore, flexible organic photovoltaics with the ZnO/Ag/ZnO electrodes demonstrate much better performance in mechanical bending tests in comparison to the performance of standard indium tin oxide-based organic photovoltaics, and the previously reported oxide/metal/oxide-based organic photovoltaics.